10-year Follow-up of Mod Quad and Triangle Tilt Surgeries in Obstetric Brachial Plexus Injury - Rahul K. Nath, MD; Chandra Somasundaram, PhD (Plastic and Reconstructive Surgery, Global Open, 2019)
Aim:. To evaluate whether obstetric brachial plexus injury (OBPI) children who had mod Quad and triangle tilt surgeries maintained their recovered upper extremity functional movements over 10 years. Background:. The short-term outcomes of surgery in OBPI patients are well documented. However, only a few publications with results over 10-year postoperative follow-up exist. We have previously reported the outcomes of these 2 surgeries in OBPI after 1, 2, and 5 years. Here, we report the successful outcomes in 17 of these patients over 10 years. Methods:. Seventeen OBPI patients, who had mod Quad, a modified muscle release operation and triangle tilt, a bony surgical procedure with us between 2005 and 2008, had postoperative follow-up of 10 years and met the inclusion criteria. Patients who had multiple surgeries and did not have 10-year follow-up are excluded in this study. Results:. Fifteen of 17 children maintain their recovered upper extremity functions for extended long period (mean, 10 years; range, 9–13 years). There was statistically significant improvement in total functional Mallet score after 3 years (mean, 18.8 ± 2.1; P ≤ 0.01) from the preoperative mean total Mallet score of 14.5 ± 1.2. This improvement was not only maintained for extended period but also improved (mean total Mallet score, 20.35 ± 2.3; P ≤ 0.01) in some patients. Conclusions:. Overall, all upper extremity functions improved greatly after mod Quad and triangle tilt surgeries in OBPI children, and they were able to maintain their recovered functional movements over extended period of 10 years.